Stratos: Virtual Middleboxes as First-Class Entities - Gember, Aaron; Akella, Aditya; Anand, Ashok; Benson, Theophilus; Grandl, Robert (University of Wisconsin-Madison Department of Computer Sciences, 2012)
Enhancing application deployments in today's clouds using virtual middleboxes is challenging due to the lack of network control and the inherent difficult in intelligently scaling middleboxes to cope with application demands. Our position is that application and middlebox composition and scaling must occur in concert, and addressing the challenges that arise requires a framework that recognizes middleboxes as first-class entities. In this paper, we present the design, implementation, and evaluation of such a framework,called Stratos, that is targeted for immediate deployment over- or under-the-cloud today. In Stratos, tenants specify rich middlebox and application topologies using high-level abstractions, and desired middlebox traversals are realized using a novel distributed programmable data plane design. To avoid degradation in middlebox performance, middleboxes are automatically scaled using a greedy heuristic to meet application demands. Under-the-cloud deployments using network-aware flow distribution and placement provide further performance and scaling benefits. Our evaluation of an over-the-cloud deployment atop EC2 and simulation of an under-the-cloud deployment shows Stratos provides significant benefits to both tenants and providers.
Keywords: scaling; cloud; middlebox